2014
DOI: 10.1186/1471-244x-14-85
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression and its associated factors among patients attending primary care settings in the post-conflict Northern Province in Sri Lanka: a cross-sectional study

Abstract: BackgroundIn Sri Lanka, civilians in the Northern Province were affected by a long-term armed conflict that ended in 2009. This study aims to describe the prevalence of depression and its associated factors among adult patients attending primary care settings in the Northern Province in Sri Lanka.MethodsWe report data from a cross-sectional patient morbidity registry established in 16 primary care facilities (12 Divisional Hospitals and 4 Primary Medical Care Units) in four districts of the Northern Province. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
4
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 39 publications
6
44
4
1
Order By: Relevance
“…The only study published was from the Northern Province of Sri Lanka in 16 primary health care facilities [11]. The findings of this study may not be generalisable to other parts of the country, given that the study had been done out in a rural area in the aftermath of an armed conflict.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…The only study published was from the Northern Province of Sri Lanka in 16 primary health care facilities [11]. The findings of this study may not be generalisable to other parts of the country, given that the study had been done out in a rural area in the aftermath of an armed conflict.…”
Section: Introductionmentioning
confidence: 76%
“…A study conducted in 12 Divisional Hospitals and 4 Primary Medical Care Units in the Northern Province reported overall prevalence of depression of 17.8% and major depression 4.5% [11]. Several other studies have looked at the prevalence of depression in different populations in Sri Lanka.…”
Section: Discussionmentioning
confidence: 99%
“…Perceptions of ill health and pain, quality of life, and functional status are consequences of depression, which itself was comparable to or exceeded the effects of other chronic diseases . Certain sociodemographic and health‐related factors, comparable to those identified in the Western world, have been associated with depression in Sri Lanka . Among them, gender, ethnicity, level of education, restricted instrumental activities of daily living, hearing difficulty, physical disability, perceived income inadequacy, and living alone were associated with elder depression …”
Section: Introductionmentioning
confidence: 93%
“…Lifestyle changes in this period can predispose them to psychological imbalances and, therefore, conditions such as depression. Evidence from some studies has demonstrated that there are higher prevalence of depression among young elders, compared to younger age groups and older elders . These studies also found that most young elders who retained physical capacity had positive mental well‐being.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation